Big data and a smarter university: a literature review - Hayikader, Sameer; Mohamad Niyaz Khan, Mohd. Toriq Khan; Ahmad Dahlan, Abdul Rahman (Research Publish Journals, 2015)
Using big data in a university is ‘the thing’ today since almost all information today is digitalized. Big data ensures better data processing, analysis and sharing, thus increasing productivity and researchers would have a great time doing their researches. A smart university is a university which uses technologies which could increase the productivity of knowledge management. Changing into a smart university is definitely a smart move because it is important to be competitive in a world full of formidable competitors. Research has proven that smart universities such as Caltech University and Northwestern University which are among the top universities in the world has also endeavored into the big data arena.